The Effective Application of Teaching English in Bilingual Program - Sylviana Stefanie (Metonimia: Jurnal Sastra dan Pendidikan Kesusastraan, 2022)
Social community nowadays is really concerned with the students’ English ability. It really impact on the teaching method, school program management and curriculum adaptation. One of the programs that applied those adjustments is the bilingual or usually called national plus program in the primary level. Thus, this research undertaking was involving a sample of 24 students who learns in 6th grade bilingual program at SD BPK Penabur Taman Holis Indah Bandung and 5 bilingual class teachers. The research investigates the application of the bilingual program in the elementary student level with the students’ limited abilities, supports and facilities in learning English as a foreign language. Based on the results exist, the teachers in this school has delivered the program effectively. This research includes the students and teachers response in involving this bilingual program with their own perspectives. The data, by using questionnaires, proved that both teachers and students think that the bilingual programs are quite effective, though; it needs a lot of efforts and better methods and strategies in running the program, so it can give the best result and effectiveness in learning English in bilingual program. Hopefully, based on this research results, the school can reflects some bilingual implementations by looking the real field response and may manage a new view of thinking in running the program. For teachers, this research can become a reflection and evaluation tools of what they’ve done in teaching. For students, this can a little bit assure them to get involved more in this program as a way of learning English as the social community demands them to. This research has proved that the teaching method that has been done effectively, though, it still needs some continuous revises.